A stretchable and compressible ion gel based on a deep eutectic solvent applied as a strain sensor and electrolyte for supercapacitors. Issue 2 (5th December 2019) - Hong, Shu; Yuan, Yang; Liu, Chaozheng; Chen, Weimin; Chen, Ling; Lian, Hailan; Liimatainen, Henrikki
Abstract : A deep eutectic solvent ion gel applied as a sensor for monitoring the grasping motion and as an electrolyte for symmetrically structured supercapacitors. Abstract : An ion gel based on a deep eutectic solvent (DES) was fabricated using free radical polymerization of an acrylamide monomer in a choline chloride–urea–glycerol (ChCl–U–G) system. The mechanical properties of the ion gel were reinforced by dispersing cellulose pulp in the DES without losing its conductivity. The obtained ion gel was flexible and strong, and it acted like an elastomer. Its excellent mechanical properties can be ascribed to the formation of a coherent hydrogen bond network between the DES and the polymer matrix. The ion gel was successfully applied as a sensor to monitor the grasping motion of the hand, which provides a new approach for designing green electronics ( e.g., for electronic skin). The ion gel was also applied as a solid-state electrolyte in a symmetric supercapacitor with a wide operating voltage window of 2 V and a high specific capacitance of 161.8 F g −1 at a current density of 0.2 A g −1 . It also exhibited a high energy density of 22.47 W h kg −1 at a power density of 0.11 kW kg −1 and outstanding cyclability (95.3% capacitance retention after 2000 cycles at 1.0 A g −1 ). Moreover, the main components of the prepared multifunctional ion gel are biocompatible, cost-effective, and environmentally friendly, offering a new route for the fabrication of green and adaptable structures for electronics.